Recent advances in innovative strategies for plant disease resistance breeding - Wang, Dekun; Yang, Ruojiao; Liu, Mengting; Li, Haolong; Li, Haitao; Yuan, Wenya; Zhang, Haitao (Frontiers in Plant Science, 2025)
Plant disease poses a great threat to crop production. The mechanisms underlying plant-pathogen interactions are critical research topics worldwide. In recent years, significant breakthrough studies have been reported, broadening our understanding of plant immunity. Based on these findings, many strategies have been developed to improve plant defense against various diseases. Here, we summarize these strategies and their applications in studies aimed at promoting crop resistance. Besides domain swapping, gene shuffling, and random mutation, three additional strategies have been developed in the last decade. The first strategy is gene editing of host susceptibility (S) genes to prevent pathogen infection. Editing of Mlo and DMR6 gene in many species are good examples of this approach. The second strategy is editing the promoters of host S genes or resistance (R) genes. This strategy is widely used to counteract Xanthomonas, such as modifying the promoters of LOB1 and SWEET genes in several crops to enhance resistance. The third strategy is designing R gene products, especially nucleotide-binding and leucine-rich repeat (NLR) receptors. This approach is based on the growing knowledge of the structural features and mechanisms of NLRs, which have seen significant advances recently. To date, all NLR-engineering attempts have focused on rice paired NLRs, such as Pikp-1/Pikp-2 (allelic to Pikm-1/Pikm-2) and RGA4/RGA5. The bioengineering of these NLRs provides a promising method to combat diverse pathogens. Detailed studies in many crops are also discussed in this review, organized around these strategies. In summary, with progresses in understanding plant immune mechanism, many innovative molecular strategies are available to mitigate the threat of plant pathogens in the future.